Modification of Shooting Kits to Improve Shooting Accuracy in MBO Petanque Students Muhammadiyah Surakarta University - Muhammad Hisbul Barokah; Nurhidayat (UNIB Press, 2022)
This study aims to determine the effect of Modified Shooting Kits on Increase Shooting in MBO Petanque UMS Students. The practice of using modified shooting kits aims to make MBO petanque when running the training program become accustomed to throwing shots on the iron. The method used in this study uses an experimental method and uses a